Timed insemination of suckled beef cows after ovulation synchronization with Cosynch + CIDR - Sandra K. Johnson; Keith R. Harmoney; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2002)
Lactating beef cows (n=360) were synchronized using the Cosynch procedure; 100 Î¼g of GnRH (day −7) followed in 7 days by 25 mg of PGF2α(day 0). A used intravaginal progesterone insert (CIDR-B) was inserted on day −7 and removed at the time of PGF2αadministration. Cows were assigned to a 2 x 2 factorial arrangement of four treatments: 1) insemination beginning at 48 vs. 60 hours after PGF2αand 2) administration of a second, 100 Î¼g injection of GnRH or an equivalent volume of saline immediately after timed AI. Timed AI at either 48 or 60 hours after PGF2αin a Cosynch + CIDR protocol was equally effective. Administration of GnRH at timed AI improved conception in all cycling cows and in some noncycling cows, depending on their progesterone status.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Ovulation synchronization; Beef cows; Timed AI; GnRH; CIDR